2017
DOI: 10.1371/journal.pone.0180293
|View full text |Cite
|
Sign up to set email alerts
|

Infection experiments with novel Piscine orthoreovirus from rainbow trout (Oncorhynchus mykiss) in salmonids

Abstract: A new disease in farmed rainbow trout (Onchorhyncus mykiss) was described in Norway in 2013. The disease mainly affected the heart and resembled heart and skeletal muscle inflammation (HSMI) in Atlantic salmon (Salmo salar L.). HSMI is associated with Piscine orthoreovirus (PRV), and a search for a similar virus in the diseased rainbow trout led to detection of a sequence with 85% similarity to PRV. This finding called for a targeted effort to assess the risk the new PRV-variant pose on farmed rainbow trout an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 41 publications
7
65
0
2
Order By: Relevance
“…The SAV PCR test targeted the nsP1 gene (Hodneland & Endresen, ) and detects both SAV subtypes (2 and 3) found in Norway (Hjortaas et al., ). The PCR test employed a method described previously (Glover, Sørvik, Karlsbakk, Zhang, & Skaala, ; Palacios et al., ) and detected the PRV‐ Salmo salar (PRV‐Ss) virus variant (Hauge et al., ). Samples giving a C t (cycle threshold) value <37.0 were considered positive.…”
Section: Methodsmentioning
confidence: 99%
“…The SAV PCR test targeted the nsP1 gene (Hodneland & Endresen, ) and detects both SAV subtypes (2 and 3) found in Norway (Hjortaas et al., ). The PCR test employed a method described previously (Glover, Sørvik, Karlsbakk, Zhang, & Skaala, ; Palacios et al., ) and detected the PRV‐ Salmo salar (PRV‐Ss) virus variant (Hauge et al., ). Samples giving a C t (cycle threshold) value <37.0 were considered positive.…”
Section: Methodsmentioning
confidence: 99%
“…Coho salmon (O. kisutch Walbaum) in Japan (Takano et al, 2016), and PRV-3 has been shown to induce heart pathology and anaemia in farmed rainbow trout (O. mykiss Walbaum) (Hauge et al, 2017;Olsen, Hjortaas, Tengs, Hellberg, & Johansen, 2015). PRV-1 is considered to infect almost all farmed Atlantic salmon during the sea phase in Norway Løvoll et al, 2012).…”
Section: Prv-2 Causes Erythrocytic Inclusion Body Syndrome (Eibs) In mentioning
confidence: 99%
“…Currently, three PRV genotypes have been described. PRV‐1 is the causative agent of heart and skeletal muscle inflammation (HSMI) in farmed Atlantic salmon in Norway (Wessel et al, ), PRV‐2 causes erythrocytic inclusion body syndrome (EIBS) in farmed Coho salmon ( O. kisutch Walbaum) in Japan (Takano et al, ), and PRV‐3 has been shown to induce heart pathology and anaemia in farmed rainbow trout ( O. mykiss Walbaum) (Hauge et al, ; Olsen, Hjortaas, Tengs, Hellberg, & Johansen, ). PRV‐1 is considered to infect almost all farmed Atlantic salmon during the sea phase in Norway (Haatveit et al, ; Løvoll et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Experimental infection studies have strengthened the association between PRV‐3 and the disease signs seen in rainbow trout (Hauge et al, ). The infection transmitted to all of rainbow trout cohabitants that also developed disease symptoms.…”
Section: Introductionmentioning
confidence: 98%